“TEACHING VOCABULARY BY USING REALIA (REAL OBJECT) MEDIA” - Kulmamatova Aziza (Western European Studies, 2024)
The Graduation project work highlights the importance of teaching vocabulary skills in our country, which is currently one of the most pressing issues in the teaching of foreign languages. The goal of teaching today is not only to listen and understand, to read, to learn new words using real objects and write texts, but also to express content in speech, to connect it with everyday life. The highest goal of the teacher is to help students master the topics given in English and to teach them the process of teaching vocabulary skills. The project work reflects the author’s understanding and analysis of communicative language teaching through small group work through experiences.
Keywords: Teaching; Vocabulary; Realia